Self-Motivated Learning on Reproductive Health Education: Literature Review - Ekawati, Rany; Fahmi Karami, Ahmad; Rini Suprobo, Nina; Putri Novembriani, Rizqie; Rahma Maulida, Adiska; Ikrimah, Ikrimah; Naya Apriliyani, Putri (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Sexual health issues remain unresolved globally and nationally. In Indonesia, unwanted pregnancies among women aged 15-19 years are twice as high (16%) as those aged 20-24 years (8%), and 19% of young people aged 15-24 who have had sexual relations report unwanted pregnancies. Comprehensive Sexuality Education (CSE) is one of the media in addressing this issue, fostering self-motivated learning that empowers adolescents to prevent unintended pregnancies and manage their sexual health. This study aimed to identify media and tools that effectively enhance adolescents' motivation for independent learning about reproductive health. A literature review was conducted using the Publish or Perish database for articles from 2018 to 2023, with keywords such as